2023
DOI: 10.1158/0008-5472.can-22-3895
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Impact of Posttranslational Modification of Glypican-3 on Liver Carcinogenesis

Abstract: Glypican-3 (GPC3) is a cell-surface glycoprotein that is frequently overexpressed in hepatocellular carcinoma. GPC3 undergoes extensive post-translational modification including cleavage and glycosylation. This review focuses on the structure and function of GPC3 in liver cancer, highlighting the post-translation modification (PTM) of the tertiary and quaternary structures of GPC3 as a potential oncogenic regulatory mechanism. We propose that the function of GPC3 in normal development can vary with extensive P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…To evaluate the selectivity of the VSCLIA, seven other cancer biomarkers, including CEA, NSE, PSA, CA125, CA199, FER, and GPC3 were selected for cross-reaction tests. All of these biomarkers are macromolecules with complex antigen epitopes existing in cancer patients, which might induce cross-reactions with VNAR in real serum detection, especially GPC3, a cell-surface glycoprotein that is frequently overexpressed in HCC like AFP . Under the optimal conditions, AFP was replaced by other biomarkers for the test of VSCLIA.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the selectivity of the VSCLIA, seven other cancer biomarkers, including CEA, NSE, PSA, CA125, CA199, FER, and GPC3 were selected for cross-reaction tests. All of these biomarkers are macromolecules with complex antigen epitopes existing in cancer patients, which might induce cross-reactions with VNAR in real serum detection, especially GPC3, a cell-surface glycoprotein that is frequently overexpressed in HCC like AFP . Under the optimal conditions, AFP was replaced by other biomarkers for the test of VSCLIA.…”
Section: Resultsmentioning
confidence: 99%
“…5H ). Finally, elevated GPC3 expression occurs in hepatocellular carcinomas with limited expression found on healthy tissues ( 35 ). A single 8 mg/kg i.v.…”
Section: Resultsmentioning
confidence: 99%
“…is a tumor fetal proteoglycan anchored to the cell membrane and is commonly detected in fetal liver but not in healthy adult liver. [ 41 , 42 ] To predict the diagnostic value of serum GPC3 in patients with HCC, a meta-analysis by Yang et al showed an association between GPC3 expression and HCC patient. [ 43 ] Another study pointed to GPC3 as a potential novel therapeutic target for osteosarcoma [ 44 ] ; Yu et al [ 45 ] found that the expression of GPC3 protein was significantly higher in lung squamous cell carcinoma than in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%